Os modos de vida de mulheres em situação de rua em Maracanaú - Câmara, Andréa Esmeraldo (2019)
The street, taken as a living space, is a field of expression of the oppressions of the capitalist mode of production. Being a woman in this scenario evokes power relations inserted in the concept of gender considered, as a social construction, and based on patriarchal relations, which condition women to private space. It starts from studies of gender relations that are based on analysis and intersectional interventions, and from unveiling the relations of subalternity in which the woman is placed. In the perspective of concretizing this presupposition, is questined the way of living of the women in street situation are constituted? Its general objective is to understand the way of living of street women from their daily lives in the public space, and as specific objectives to describe the way of living of street women in Maracanaú; analyze prejudices and stigmata in women's lives; to analyze the processes of resistances in the confrontation with the stigmas and prejudices experienced by women in the street situation. A qualitative research was carried out using qualitative research, with interviews with 7 women in the Pop Center of Maracanaú, whose material was submitted to Content Analysis from Bardin's perspective, and Atlas Ti 5.2 software. The results showed the relationship of oppressive systems, especially stigmas and prejudices, and of resistance processes in the construction of the livelihoods of women in the street situation. Thus, it is observed that in the livilihood of women in the street, poverty is a significant marker for the maintenance of this situation, which comes from a diversity of trajectories and reasons for breaking with the domestic space. This entails an extension of the notion of territory that goes through the relationship with the forces of a policy that can take place outside the law. The Violence has presented itself as a significant experience that marks the way of life of women on the street, and the category of oppression is present in the stigmas and prejudices that act by disqualification and discredit leading to feelings of humiliation and shame. Livelihoods contain modes of resistance, even though public policies are limited to these women, and they prioritize individualized solutions to their needs.